Efficient total synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid - Pandey, Satyendra Kumar; Kumar, Pradeep (European Journal of Organic Chemistry, 2007)
An efficient enantioselective synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid (1) from epichlorohydrin is described. The key steps include Jacobsen's HKR, Sharpless asymmetric dihydroxylation, regioselective opening of epoxide and cyclic sulfate. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: cyclic sulfate; Dihydroxylation; Grignard reaction; hydroboration-oxidation; Jacobsen's hydrolytic kinetic resolution (HKR); regio selectivity